The effect of manager mobbing behaviour on female employees’ quality of life - Kara, D.; Kim, H.; Uysal, Muzaffer (Routledge, 2015)
© 2015 Taylor & Francis The purpose of this paper is to examine the effect of manager mobbing behaviour on female employees’ quality of working life and overall quality of life. A mobbing behaviour may be a long-term hostile behaviour detected in employees at workplaces. A total of 373 female employees who work in five-star hotels in Turkey participated in this study. First, correlation analysis was performed between manager mobbing behaviour and female employees’ quality of working life, and overall quality of life. The results of the study revealed that there was a negative correlation between manager mobbing behaviour and female employees ‘quality of life. Second, the structural equation model was applied to analyse the relationship among these three constructs. The results of this analysis showed that managers’ mobbing behaviour has a significant negative effect on female employees ‘quality of working life and overall quality of life. In addition, employees’ quality of working life influences their overall quality of life.